Polarization-insensitive integration of nanoparticle-on-a-slit cavities with dielectric waveguides for on-chip surface enhanced Raman spectroscopy - Javier Redolat; Daniel Arenas-Ortega; Ángela Barreda; Amadeu Griol; Elena Pinilla-Cienfuegos; Alejandro Martínez (npj Nanophotonics)
Abstract In the nanoparticle-on-a-slit (NPoS) cavity, a variation of the nanoparticle-on-a-mirror geometry, a metallic nanoparticle is placed on a functionalized narrow slit created on a metal plate so that two nanometric-scale gaps enable extreme plasmonic localization. For many applications, it is desirable to integrate such cavities on a chip and provide access to (and collection from) the hot spots via integrated waveguides. In this work, we propose, design, and experimentally demonstrate the efficient integration of NPoS cavities with dielectric waveguides on a silicon-based chip. We show that both the fundamental TE and TM modes of silicon-nitride slot waveguides can drive the cavity, making our device polarization-insensitive. We demonstrate our concept by performing surface-enhanced Raman spectroscopy of BPT molecules on a chip fabricated by standard silicon processes mixed with the deterministic positioning of gold nanospheres on the gap of a plasmonic dipole, which remarkably can also work as an infrared antenna.